2003
DOI: 10.1002/pola.10715
|View full text |Cite
|
Sign up to set email alerts
|

Roles of rhenium diimine complexes as metal‐ion probes and photosensitizers in functional polyurethanes

Abstract: Polyurethanes incorporated with rhenium diimine complexes were synthesized. The polymers exhibited interesting morphologies and solution properties. Results from gel permeation chromatography suggested the formation of polymer aggregates in solutions. The polymers could act as probes for metal ions. The addition of metal ions to polymer solutions led to significant changes in the electronic absorption properties of the polymer solutions. This was attributed to the interactions between the polyether moieties an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…The first peak corresponds to ultrahigh-molecular-weight (>10 7 ) species, while the second peak carries several small shoulders with a calculated number-average molecular weight of 176 000. Such phenomenon was also observed in our previously reported rhenium [8] or ruthenium complex containing polymers. [9] This may be caused by an interaction between the charged polymers and the column materials, or by the formation of aggregates in polymer solution.…”
Section: Resultssupporting
confidence: 64%
“…The first peak corresponds to ultrahigh-molecular-weight (>10 7 ) species, while the second peak carries several small shoulders with a calculated number-average molecular weight of 176 000. Such phenomenon was also observed in our previously reported rhenium [8] or ruthenium complex containing polymers. [9] This may be caused by an interaction between the charged polymers and the column materials, or by the formation of aggregates in polymer solution.…”
Section: Resultssupporting
confidence: 64%
“…Those samples doped with TPA had primary yields one order of magnitude higher than that of the undoped sample, and this indicated the active role of TPA in the excitation process. On the other hand, their thermalization distances were very similar to those of other rhenium complexes70 and rhenium‐containing polymers 74. This suggested that the values of the initial separation distance were largely dependent on the rhenium center.…”
Section: Resultssupporting
confidence: 60%
“…[177][178][179][180][181][182] Rhenium(I) diimine complexes have been incorporated into polymeric structures based on polystyrene, 183 poly(methyl methacrylate), 183 poly(p-phenylenevinylene) 20,23,184 and polyurethane. 185 However, only a few articles deal with the structure-property relationships of conjugated Re(I)-containing polymers. 23,186,187 Schanze et al selected, as targets, a series of oligo(arylene ethynylene)s (OAEs) that contained a central 2,2 0 -bipyridine metal chelating unit.…”
Section: Macromolecules Containing Pyridine-based Re(i) Complexesmentioning
confidence: 99%